Use of CsPbX3 nanocrystals as an additive in organic solar cell for efficiency improvement - Çisem Kırbıyık Kurukavak; Mütahire Tok (Results in Surfaces and Interfaces)
Here, we aimed to investigate the dependence of organic solar cells (OSCs) performance on the CsPbX3 perovskites nanocrystals (PNCs). The effect of presence of CsPbX3 (X = Cl, Br, and I) NCs in photoactive layer was studied using various characterization techniques. UV–Vis spectroscopy and XRD patterns of P3HT:PCBM thin films showed that the light harvesting, crystallinity and phase separation increased by the introducing PNCs, which improved the electrical properties. The AFM images supported the improved crystallinity of P3HT and homogeneous structure of photoactive layer. OSCs with the configuration of ITO/PEDOT:PSS/P3HT: PCBM: PNCs/LiF/Al were fabricated. The PNCs incorporation resulted to efficiency enhancement from 1.75 % to 2.88 % (P3HT:PCBM - CsPbBr3). The increase in efficiency was strongly related to the improved current density (Jsc) (10.75 mA cm−2) and open-circuit voltage (Voc) (0.598 V).